National Museum of Indonesia : Virtual Tour Experience - Nazhar, Ryanty Derwentyana (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This article aims to discuss the implementation of exhibition spaces in virtual tour museums in Indonesia. The case study taken is the National Museum of Indonesia, the largest museum in Indonesia and has many collections. In 2020 the Covid-19 pandemic occurred globally, including in Indonesia, which limited activities in public facilities. One of the effects of this incident was the closure of museum facilities. The National Museum of Indonesia is one of the museums that has finally opened an online virtual tour facility to deal with the ongoing Covid-19 pandemic problem. In the exhibition interior design science, there are several elements and design systems applied to get the things they want when visiting an exhibition, including getting clear information and education and experiencing the recreation obtained from space’s activities and atmosphere. The virtual exhibition space will undoubtedly be different from the conventional exhibition space. The research carried out a method by collecting data based on a survey of 121 respondents, who conducted a virtual tour of the museum directly and assessed the room’s situation and the clarity of the information obtained. This study’s results are in the form of experiences experienced and felt by visitors, which can be used as input for the improvement of the virtual tour of the National Museum of Indonesia in particular, and museums in Indonesia in general.